The role of MMPs in intracerebral hemorrhage - Guan, Xiaofei; Li, Meiren; Li, Huimin; Guo, Zeqin; Ullah, Muhammad Saad; Liu, Xiaoqun; Wu, Moxin; Yu, Wenmin (Frontiers in Cell and Developmental Biology, 2025)
Intracerebral hemorrhage (ICH) is characterized by the disruption of cerebral vascular integrity, leading to hematoma enlargement, edema formation and physical damage to brain tissue. It has an extremely high disability rate and mortality rate, with mortality rates as high as 50%, imposing considerable physical and economic burdens on patients and their families. Therefore, identifying effective therapeutic targets for ICH has become an urgent issue. In recent years, numerous animal and clinical studies have shown that matrix metalloproteinases (MMPs), particularly MMP-9 and MMP-2, are closely associated with the pathophysiological processes of ICH. During the acute phase of ICH, MMP expression increases, leading to the disruption of the blood-brain barrier (BBB), exacerbating neuroinflammation and cerebral edema. However, in the subacute and chronic phases, MMPs play a crucial role in BBB repair, angiogenesis, and neurological recovery. Therefore, MMPs hold promise as effective therapeutic targets for ICH. This article provides an overview of ICH, the primary structure, classification, regulation, and role of MMPs in the destruction of the BBB, angiogenesis, and neural repair in ICH.